Preemptive veno-venous ECMO support in a patient with anticipated difficult airway: A case report. (2020) - Chakalov, I.; Harnisch, L.O.; Meyer, A.C.; Moerer, O.
Abstract: This report presents a case of endotracheal metastasis in which elective veno–venous extracorporeal membrane oxygenation (VV ECMO) was used to undergo tracheal laser-surgery prior to establishment of a definitive airway. Specifically, we describe the respiratory and airway management in an adult patient from the preclinical phase throughout elective preoperative ECMO implantation to postoperative ECMO weaning and decannulation in the Intensive Care Unit. This case report lends further supports to the idea that the extracorporeal membrane oxygenation could be electively used to provide safe environment for surgery in situations where the standard maneuvers of sustaining adequate gas exchange are anticipated to fail.